Advances in Religion, Cognitive Science, and Experimental Philosophy, edited by Helen De Cruz and Ryan Nichols. (9th November 2018) - Kvandal, Halvor
Abstract : Advances in Religion, Cognitive Science, and Experimental Philosophy, edited by Helen De Cruz and Ryan Nichols, Bloomsbury, 2016. Advances in Experimental Philosophy series. 221pp. 42.95 USD ISBN: 978-1-47422- 382-9